2001
DOI: 10.1002/dvdy.1207
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of endothelial PAS protein 1 with essential angiogenic factors suggests its involvement in human vascular development

Abstract: Endothelial PAS protein 1 (EPAS1) is a bHLH-PAS transcription factor involved in cellular response to hypoxia. Its precise role in angiogenesis is unclear, but several genes essential to vascular development, including those encoding vascular endothelial growth factor (VEGF), its receptor VEGFR-2 and Tie2, are thought to be targets of EPAS1. To investigate whether this transcription factor and its putative targets were expressed concomitantly, we performed in situ hybridization on serial adjacent sections of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The hypoxically regulated transcription factors HIF-1a and HIF-2a are overexpressed in a large number of human tumor types, including brain, prostate, breast, RCC, pheochromocytomas, astrocytomas, and non-small cell lung cancers (21,(42)(43)(44), consistent with the idea that each contributes to tumor growth by activating the expression of critical target genes. Although both HIF-1a and HIF-2a are expressed in many of the same human tumors and tumor cell lines (29,45), the relative contribution of each protein to tumor initiation and progression has been difficult to determine.…”
Section: Discussionsupporting
confidence: 57%
“…The hypoxically regulated transcription factors HIF-1a and HIF-2a are overexpressed in a large number of human tumor types, including brain, prostate, breast, RCC, pheochromocytomas, astrocytomas, and non-small cell lung cancers (21,(42)(43)(44), consistent with the idea that each contributes to tumor growth by activating the expression of critical target genes. Although both HIF-1a and HIF-2a are expressed in many of the same human tumors and tumor cell lines (29,45), the relative contribution of each protein to tumor initiation and progression has been difficult to determine.…”
Section: Discussionsupporting
confidence: 57%
“…As an illustration, EPAS1 or CALB3 were found to be up-regulated in the IC and the C areas of SCNT recipient cows respectively. EPAS1 (also known as HIF-2 ␣) is a transcription factor participating to the cellular response to hypoxia, stabilizing the vascular maturation in human angiogenesis (19) and increased with preeclampsia in women endometrium (20). The role of EPAS1 in the bovine placentation is not yet established but EPAS1 up-regulation in SCNT pregnancies is in keeping with the increase of HIF-1␣ recently reported in bovine SCNT pregnancies at day 30 (21).…”
Section: Discussionmentioning
confidence: 89%
“…HIF-1␣ and HIF-2␣ are overexpressed in a large number of human tumor types, including brain, breast, RCC carcinomas, pheochromoctyomas, astrocytomas, and non-small-cell lung cancers (Favier et al 2001;Giatromanolaki et al 2001;Jaakkola et al 2001;Khatua et al 2003). Several experiments have shown that expression of HIF-2␣ promotes more rapid growth of RCC xenografts (Kondo et al 2002(Kondo et al , 2003Maranchie et al 2002;Raval et al 2005) and ES cell-derived teratomas (Covello et al 2005) than does expression of HIF-1␣.…”
Section: Discussionmentioning
confidence: 99%